Improvement of Students’ Mathematical Critical and Creative Thinkingabilities Through Problem-Based Learning Approaches with SIDIA Software - Nur Hasanah; Solfema Solfema; Hendra Syarifuddin; Farida Farida (Postgraduate School, Universitas Negeri Padang, 2021)
The ability to mathematically thinkingcritically and creatively is a very important skill for every student in learning mathematics. To improve this ability, it is necessary to have a learning approach that allows students to make observation and exploration in order to build their own knowledge. In general, three-dimensional geometry is difficult to explain by teachers in class and difficult for students to understand. Problem-based learning with SIDIA software is one of the lessons that can be applied in the class. The main objective of this research on three-dimensional geometry is to examine the increase in critical thinking and mathematical creative abilities between students who receive SIDIA software-assisted problem-based learning and students who receive conventional learning, the relationship between mathematical critical and creative thinking abilities, and students' attitudes towards this learning. The subjects of this research are the students of SMA Negeri in Padang City with a sample of class X students. Based on the results of the data analysis, it showed that students who received problem-based learning assisted by SIDIA software are better than students who received conventional learning. There is a significant relationship between the ability to mathematically thinkingcritically and creative, and in general students who get problem-based learning assisted by SIDIA software show a positive attitude.